Broodstock management and egg and larval quality (Blackwell Science, 1995)
Broodstock Management and Egg and Larval Quality has been written as a standard text for commercial practitioners and students of aquaculture, fish biology and fisheries and provides a comprehensive review of current and future methods of broodstock and hatchery management. The range of marine and freshwater tropical and temperate finfish species considered, together with contributions from many of the world's most eminent fish biologists, provide comprehensive and international coverage of this increasingly important area of aquaculture.